Pendidikan Agama Islam bagi Anak dalam Keluarga - Hidayat, Herman Somantri; Rahmi, Nina; Mauludin, Hilman (TSAQOFAH, 2024)
The family plays an important role in Islamic religious education for children. As the first environment for children, the family has a big influence in forming character, values and understanding of the Islamic religion in the family. This research aims to examine the role of parents and other family members in instilling Islamic values in children through daily practices at home. The research method used was literature study and participant observation on several Muslim family members. The research results show that the example of parents in the family, the habit of worship, and the creation of an Islamic environment in the family are key factors in Islamic religious education for children. Parents act as the main teachers by providing teaching, guidance, and facilitating children in studying the Koran and other religious practices. The support and involvement of all family members is very important in strengthening the internalization of Islamic values in children. This research concludes that the active role of the family determines the success of Islamic religious education for children from an early age.